Enhanced model for ergonomic evaluation of information systems: application to scientific research information system - Khaoula Benmoussa; Majida Laaziri; Samira Khoulji; Kerkeb Mohamed Larbi; Abir El Yamami (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Considering the importance of the ergonomic aspect for information systems in providing an easy use of the computing systems, this paper focuses on the elaboration of a hybrid model for the ergonomic evaluation of information systems that merges a set of inspection dimensions such as accessibility, practicality, emotionality, and technological persuasion. Details on how the model has been constructed and data have been collected are presented. For the evaluation of our model, a situation of an information system for scientific research (SIMArech) in Moroccan Universities has been studied. This model can be used by ergonomist and human factor professionals. It is found that the proposed heuristics can effectively assess the most important dimensions of scientific research information systems.